Rethinking Resilience through a Comprehensive Review of Persistent Challenges in Natural Disaster Management in Southeast Asia - Desi Eka Putri; Hary Febrianto; Andri Yanto; Nina Ismayani (Geosfera: Jurnal Penelitian Geografi, 2025)
Southeast Asia is a global hotspot for natural disasters, where escalating frequency and severity, amplified by climate change, continuously test national and local resilience. This comprehensive review synthesizes and expands upon existing systematic analyses of disaster management in the region, offering a deep-dive exploration of persistent challenges. Building on a foundational systematic review that identified key literature (Samad et al., 2025), this article moves beyond simple identification to provide a deep, integrative discussion of the critical obstacles hindering effective disaster risk reduction (DRR). We analyze eight major thematic challenges: (1) inadequate preparedness, (2) inefficient response mechanisms, (3) deep-seated socio-economic vulnerabilities, (4) gaps in public education and risk perception, (5) fragile and exposed infrastructure, (6) economic constraints and resource misallocation, (7) fragmented government policies and governance, and (8) the complex role of local beliefs and culture. This review synthesizes findings from across the region, drawing on key studies from Indonesia, the Philippines, Thailand, Vietnam, and others. The analysis underscores the profound interconnectedness of these challenges, arguing that single-domain solutions are insufficient. The findings form the basis for a robust discussion on integrated policy-making, strategic investment, and community-centric approaches, concluding with actionable recommendations for scholars and practitioners to foster a more sustainable and resilient future for the region.